Annual Crop Residue Production and Nutrient Replacement Costs for Bioenergy Feedstock Production in United States. (1st May 2013) - Chatterjee, Amitava
Abstract : One billion megagrams of cellulosic feedstock will be needed to meet the target of bioenergy production by 2030. Most of these feedstocks will be from crop residues. Crop residues are the source of nutrients in agroecosystems, and their removal for bioenergy production may threaten soil sustainability. Nutrient replacement costs to replenish the N, P, and K removals were estimated for different crops across 10 U.S. farm regions. In the United States, 518 Tg (1 Tg = 10 12 g) of crop residues were produced annually based on 5‐yr (2007–2011) average crop production data. Corn ( Zea mays L.), wheat ( Triticum aestivum L.), and soybean [ Glycine max (L.) Merr.] contributed 61, 12, and 16% of the total production, respectively. Soybean residues had the lowest nutrient replacement cost of US$17 Mg −1 of residue biomass, whereas the cost significantly increased for tuber crops such as sugarbeet ( Beta vulgaris L. ssp. vulgaris, US$92 Mg −1 ) and potato ( Solanum tuberosum L., US$71 Mg −1 ). Considering production and nutrient replacement cost, soybean and wheat are two potential sources of bioenergy feedstocks.